Hubungan Self Confidence Dengan Kemampuan Komunikasi Matematis Siswa Kelas VIII SMP Negeri 1 Praya Barat Daya Tahun Ajaran 2019/2020 - Ilmi, Ilmiatirrafiah; Sarjana, Ketut; Wahidaturrahmi, Wahidaturrahmi (Indonesian Publication Center, 2021)
This study aims to determine whether there is a significant relationship between self-confidence and mathematical communication skills of students of class VIII of SMPN 1 Southwest Praya in the academic year 2019/2020. This research is an ex-post facto research. The population of this study was all students of class VIII of SMPN 1 Southwest Praya with the study sample used was the entire population taken with saturated sampling technique. Data collection techniques in this study used self confidence questionnaire instruments and mathematical communication skills tests. Data were analyzed using Microsoft Excel 2013 software with Pearson product moment correlation analysis technique. The results of data analysis show that self confidence and mathematical communication skills are included in the level of strong relationships and have a positive relationship, meaning that if self confidence is good, then mathematical communication skills are also good, and vice versa if self confidence is lacking, then mathematical communication skills are also lacking. The results of the hypothesis show that there is a significant relationship between self confidence and mathematical communication skills of students of class VIII of SMPN 1 Southwest Praya in the academic year 2019/2020.